Social Institutions, Imperfect Information, and the Distribution of Income: Reply - Starrett, David (Quarterly Journal of Economics, 1978)
Journal Article Social Institutions, Imperfect Information, and the Distribution of Income: Reply Get access David Starrett David Starrett Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 92, Issue 1, February 1978, Pages 185–186, https://doi.org/10.2307/1886006 Published: 01 February 1978